Breastfeeding Mothers' Use of Foods, Beverages, and Herbal Supplements to Increase Breast Milk Production and Associated Information Seeking Behaviors. (14th June 2022) - Ryan, Rachel; Bihuniak, Jessica; Lyndon, Audrey; Hepworth, Allison
Abstract: Objectives: Information seeking behaviors may influence how breastfeeding mothers respond to perceived insufficient milk, a primary reason for early breastfeeding cessation. The objectives of the current study were to describe where breastfeeding mothers obtained information about milk supply, and to explore whether aspects of information seeking behavior were associated with the use of foods, beverages, and herbal supplements as galactagogues. Methods: Data for the current study were collected using a cross-sectional online survey. Facebook advertisements were used to recruit women who were currently breastfeeding a singleton child and living in the United States. Participants self-reported if they ever used foods/beverages (yes, no) and herbal supplements (yes, no) to increase their breast milk production. Additional questions assessed sources of milk supply information, eHealth literacy (eHEALS), website credibility assessment practices (Hargittai Internet Credibility Index), and general credibility assessment. Multivariable logistic regression models estimated associations between information seeking characteristics and the use of foods/beverages and herbal supplements, while adjusting for select demographic and breastfeeding characteristics. Results: A total of 1123 breastfeeding mothers (non-Hispanic white = 81%; first time breastfeeding = 47%; WIC participant = 21%) were included in the analysis. Lactation consultants (68%), Facebook (61%), search engines (50%), websites (47%), and nurses (41%) were the most common sources of information about milk supply. Results from adjusted models revealed that select sources of milk supply information and general credibility assessment were associated with the use of foods, beverages, and herbal supplements as galactagogues ( p  < 0.05). Conclusions: These findings are relevant to the development and dissemination of breastfeeding education programming that aims to provide breastfeeding mothers with information about strategies that support breast milk production. Funding Sources: None.